PERANCANGAN SISTEM INFORMASI GEREJA BERBASIS WEBSITE MENGGUNAKAN FRAMEWORK LARAVEL (Studi Kasus: HKBP Sultan Mazmur Pancawati) - Sinambela, Annabella Dian Dameria; Prihandani, Kamal; Rozikin, Chaerur (Jurnal Informatika dan Teknik Elektro Terapan, 2024)
Currently, many churches still use paper or booklets for worship events, which causes paper usage to be very high and inefficient. Based on observations and questionnaires with church members, many feel this method is inefficient as paper is often only used once and then discarded. The church's internal assessment also showed this method resulted in a waste of resources and lack of easy access to information. To address these issues, a dedicated website is needed for HKBP Sultan Psalm Pancawati to deliver information efficiently and effectively. This research designs and develops a web-based church information system using the SDLC method with a prototype approach, involving mutual interaction between developers and users. The steps include needs identification, rapid design, prototype building, system development and testing, and implementation. Testing is done through alpha and beta testing, where alpha testing checks internal smoothness and beta testing uses questionnaires to evaluate external acceptance. Results showed a level of feasibility with a score of 91%, reflecting positive acceptance from users and the effectiveness of the system in meeting the needs of the congregation as well as reducing reliance on paper usage.